Gamblers' beliefs about responsibility for minimizing gambling harm: Associations with problem gambling screening and gambling involvement. (March 2021) - Gray, Heather M.; Louderback, Eric R.; LaPlante, Debi A.; Abarbanel, Brett; Bernhard, Bo J.
Highlights: Most gamblers hold individual gamblers responsible for minimizing gambling harm. Most do not hold other stakeholders (e.g., scientists, clinicians, government regulators) responsible. People who screen positive for problem gambling hold more stakeholders responsible. These responsibility beliefs appear to be unrelated to gambling involvement. Abstract: Increasingly, gambling stakeholders communicate that minimizing gambling harm is a shared societal responsibility. Individual gamblers' beliefs about responsibility for minimizing gambling harm are worthy of study because these beliefs might influence gambling behavior. In this study, using a sample of casino loyalty program subscribers ( N  = 4, 795), we observed that respondents who had a positive result on a brief gambling disorder screen were more likely than those who screened negative to hold seven stakeholder groups (i.e., scientists, clinicians, casino employees, government regulators, public health officials, casino industry lobbyists, public safety officials) responsible for helping to minimize gambling harm. The sum of stakeholder groups held responsible for minimizing gambling harm, along with beliefs that casinos share responsibility for encouraging responsible gambling behavior, predicted gambling disorder screening status after controlling for established problem gambling risk factors. These results replicated our previous study using a mostly independent sample. Contrary to our expectations, beliefs about responsibility for mitigating gambling harm were mostly unrelated to measures of gambling involvement. These results provided additional support for the notion that those who are at risk for gambling harm are especially likely to hold others responsible for minimizing such harm. However, they call into question the role of gambling involvement in this relationship.